Early mobilisation of ventilated patients in the intensive care unit: A survey of critical care clinicians in an Australian tertiary hospital. Issue 2 (March 2020) - Lin, Frances; Phelan, Sonja; Chaboyer, Wendy; Mitchell, Marion
Abstract: Introduction: Mobilising mechanically ventilated patients is safe and beneficial and improves outcomes. However, early mobilisation is not widely practiced and barriers to its implementation still exist. Objective: The objective of this study was to assess clinician perceptions, knowledge, attitudes, and behaviours towards mobilising critically ill ventilated patients in the intensive care unit, as well as perceived barriers and facilitators towards mobilisation. Methods: A prospective questionnaire based on three existing questionnaires was administered to nurses, physicians, and physiotherapists from a single mixed medical/surgical intensive care unit in an Australian tertiary hospital. The 32-item questionnaire focused on knowledge, attitudes, behaviour, and perceived facilitators and barriers. Various response options were used, and data were analysed using descriptive statistics. Results: The overall response rate was 56.6% (82 of 145). Overall, clinicians' knowledge score was 4.1 (standard deviation = 1.4) out of a possible score of 6. Early mobilisation was not perceived as a top priority by 40.2% of participants. One important facilitator was that majority of the participants perceived early mobilisation was important. The most common perceived barriers to early mobilisation were medical instability, delirium, sedation, and limited staffing. Clinicians' opinions varied on the timing and appropriateness for instituting early mobilisation. Conclusions: Clinicians had various levels of knowledge on early mobilisation as a therapy for critically ill patients. Most clinicians believed that early mobility was important and were willing to reduce sedation; however, several key barriers were identified which need to be addressed by using targeted interventions. This will reduce or close the gap between knowledge and practice.